Tissue texture extraction in indocyanine green fluorescence imaging for breast-conserving surgery. (25th February 2021) - Leiloglou, Maria; Chalau, Vadzim; Kedrzycki, Martha S; Thiruchelvam, Paul; Darzi, Ara; Leff, Daniel R; Elson, Daniel S
Abstract: A two-camera fluorescence system for indocyanine green (ICG) signal detection has been developed and tested in a clinical feasibility trial of ten patients, with a resolution in the submillimetre scale. Immediately after systemic ICG injection, the two-camera system can detect ICG signals in vivo (∼2.5 mg l − 1 or 3.2 × 10 − 6 M). Qualitative assessment has shown that the fluorescence signal does not always correlate with the cancer location in the surgical scene. Conversely, fluorescence image texture metrics when used with the logistic regression model yields good accuracy scores in detecting cancer. We have demonstrated that intraoperative fluorescence imaging for resection guidance is a feasible solution to tackle the current challenge of positive resection margins in breast conserving surgery.